Use of thrombocyte count dynamics after aneurysmal subarachnoid hemorrhage to predict cerebral vasospasm and delayed cerebral ischemia: a retrospective monocentric cohort study - Jan Oros; Stefanos Voglis; Ferdinand Oliver Bohmann; Lina Elisabeth Qasem; Christophe Théo Arendt; Fee Keil; Wolfgang Miesbach; Marcus Czabanka; Sarah Christina Reitz (Scientific Reports)
Abstract Cerebral vasospasm (CVS) and delayed cerebral ischemia (DCI) are critical complications following aneurysmal subarachnoid hemorrhage (aSAH), contributing to substantial morbidity and mortality. This retrospective cohort study investigated thrombocyte count (TC) dynamics as a potential marker for predicting CVS and DCI in 233 adult patients with aSAH. Parameters including TC, C-reactive protein, hematocrit, CVS, and DCI were analyzed using logistic regression, Spearman correlation, and time-to-event analysis. CVS and DCI occurred in 71.1% and 41.2% of patients, respectively. A relative thrombocyte count decrease greater than 12.6% within the early post-aSAH period was significantly associated with increased risks of CVS (p < 0.001; 95% CI 4.74–25.3) and DCI (p = 0.003; 95% CI 1.39–5.43). Temporal analysis revealed that greater TC decrease correlated with earlier CVS onset (p = 0.00016; R=-0.28), with a median of three days from the minimum TC to CVS onset. This association suggests a potential diagnostic window for early detection and intervention if validated in prospective studies.